PERSEPSI KARYAWAN TERHADAP KOMITMEN ORGANISASIONAL: AKTIVITAS TANGGUNG JAWAB SOSIAL PT BANK CENTRAL ASIA, TBK CABANG MALANG - Lidia Halim; Sumiati Sumiati; Mintarti Rahayu (Ma Chung Press, 2016)
Corporate social responsibility agenda currently gained attention by stakeholders because it cause a profit such as retaining employees. The purpose of this study was analyze the impact of employee’s perceptions on corporate social responsibility activities to the organizational commitment which moderated by employee involvement. The sample of this research were employees on Main Branch Office “Borobudur” PT Bank Central Asia in Malang by using total sampling. According to SEM- PLS analysis employee’s perceptions on corporate social responsibility activities has direct effect on organizational commitment and employee involvement moderating employee perceptions of corporate social responsibility activities to the organizational commitment.